2016
DOI: 10.1007/s00702-016-1658-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screening of PLA2G6 in Japanese patients with early onset dystonia-parkinsonism

Abstract: A recessive mutation in PLA2G6, which is known to cause infantile neuroaxonal dystrophy (INAD) and neurodegeneration associated with brain iron accumulation (NBIA), has recently been shown to be responsible for PARK14-linked dystonia-parkinsonism. To study the frequency of PLA2G6 mutations, including those caused by gene rearrangement in patients with parkinsonism, we performed direct sequencing and investigated copy number variations (CNVs) of this gene in 109 Japanese patients with parkinsonism. Direct seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Cardiac uptake of meta‐iodobenzylguanidine, a physiological analog of norepinephrine, was reduced. Genetic analysis of these siblings revealed a homozygous mutation of p.A499T (c. 1495G>A), as reported previously . The patient died of sepsis at the age of 48.…”
supporting
confidence: 73%
“…Cardiac uptake of meta‐iodobenzylguanidine, a physiological analog of norepinephrine, was reduced. Genetic analysis of these siblings revealed a homozygous mutation of p.A499T (c. 1495G>A), as reported previously . The patient died of sepsis at the age of 48.…”
supporting
confidence: 73%
“…Eyelid-opening apraxia was reported in six cases. 8,24,25,55 Dysarthria was described in 29/30 (96.7%; Fig. 1E) cases.…”
Section: Phenotypementioning
confidence: 97%
“…Taking into account the information on all the PLAN-DP patients published to date, we found that NMS are very frequent in this condition, evident in more than 80% of patients. NMS preceded the diagnosis of parkinsonism in 46% of patients [ 4 , 16 , 18 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 38 ], sometimes even 20 years earlier. Unlike idiopathic Parkinson´s disease (iPD) in which hyposmia, REM sleep behavior disorder, depression and constipation are the most frequent premotor symptoms [ 39 ], neuropsychiatric symptoms dominate the clinical landscape in pre-motor PLAN-DP.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, impaired cognition was the most frequent NMS, evident in 64% of patients [ 4 , 7 , 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 28 , 29 , 32 , 33 , 37 , 38 ]. This phenomenon was detected before PD diagnosis usually manifested as school failure [ 4 , 18 , 24 , 25 , 29 ] and after the diagnosis of parkinsonism. Memory complaints are frequent in early iPD [ 39 ], although cognitive changes are usually subtle [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation